Rattus korinchi - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Rattus korinchi (Robinson and Kloss, 1916). J. Str. Br. Roy. Asiatic Soc., 73:275. TYPE LOCALITY: Indonesia, W Sumatra, Propinsi Jambi, Gunung Kerinci, Sungai Kring, 7300 ft. DISTRIBUTION: Recorded only from Gunung Kerinci and Gunung Talakmau in W Sumatra (see map in Musser, 1986:4). COMMENTS: Revised by Musser (1986). Known by very few specimens, and morphologically unlike any other described species of Rattus. Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 654, DOI: 10.5281/zenodo.7353098